2018
DOI: 10.3892/ol.2018.9021
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of puerarin on angiotensin II‑induced aortic aneurysm formation by the inhibition of NADPH oxidase activation and oxidative stress‑triggered AP‑1 signaling pathways

Abstract: Puerarin, an active ingredient of , has a range of pharmacological effects and excellent pharmacodynamic properties. In the present study, the effect of puerarin on angiotensin II-induced aortic aneurysm formation and the potential underlying molecular mechanisms were examined. The results revealed that puerarin significantly suppressed the viability, and induced the apoptosis, of aneurysm-inducing cells in a time- and dose-dependent manner. Furthermore, treatment with puerarin significantly suppressed the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Puerarin (1) was also investigated for its hypotensive effects and mechanisms in spontaneously hypertensive rats [12]. The effect of puerarin (1), isolated from P. lobata, on angiotensin II-induced aortic aneurysm formation was also investigated [13]. Although puerarin (1) was reported for its antidepressant-like effects in the chronic unpredictable stress-induced rats [14], its effects on depressive-like symptoms and neurogenesis in OVX mice, the animal model for menopause, have never been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Puerarin (1) was also investigated for its hypotensive effects and mechanisms in spontaneously hypertensive rats [12]. The effect of puerarin (1), isolated from P. lobata, on angiotensin II-induced aortic aneurysm formation was also investigated [13]. Although puerarin (1) was reported for its antidepressant-like effects in the chronic unpredictable stress-induced rats [14], its effects on depressive-like symptoms and neurogenesis in OVX mice, the animal model for menopause, have never been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Occurrence of oxidative stress enhanced the content of MDA while reducing the activities of antioxidant enzymes including SOD and CAT, which are crucial antioxidant enzymes in the defensive system under oxidative stress condition and they together resist the HRECs to HG-induced cell death (Xiao et al 2020). The inhibitory effects of puerarin on oxidative stress have been reported in a large number of studies (Wu et al 2014;Xue et al 2016;Wang et al 2017;Yue et al 2018). It has been reported that puerarin inhibits HG-induced MCP-1 expression in cultured endothelial cells (Han et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB plays key roles in response to various stress stimuli and is the main regulator and initiator of inflammatory response ( 46 48 ). Together with AP-1, the activated NF-κB participated in many cellular processes, including apoptosis, proliferation, and differentiation ( 49 ). The factors of TNF-α, IL-1β, IL-6, and IL-8 are in synergy with cytokines, which are messengers of the inflammatory cascade ( 50 , 51 ).…”
Section: Discussionmentioning
confidence: 99%